ANALYSIS OF ACADEMIC PERFORMANCE TIME MANAGEMENT AND ACHIECVEMENT - Harun Samsudin; Ade Risna Sari; Muh Akob; Angga Kurniawan (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this research is to find out whether the time management variable has an influence on student academic achievement. The research data uses primary data derived from questionnaires which are then processed and analyzed and then presented in the form of tables and narratives. The sample used was 97 respondents taken from the second semester student population majoring in Management who already had study results in the form of grades and stated in the study results card. The sampling technique used is non-probability sampling. In this research, tthe analysis technique used is Multiple Linear Regression Analysis. The results of the study stated that time management has a positive influence on academic achievement.